Pump position and thrombosis in ventricular assist devices: Correlation of radiographs and CT data. Issue 12 (December 2021) - Aigner, Philipp; Schlöglhofer, Thomas; Plunger, Lea Carmen; Beitzke, Dietrich; Wielandner, Alice; Schima, Heinrich; Zimpfer, Daniel; Moscato, Francesco
Malpositioning of left ventricular assist devices (LVAD) is a risk factor for thrombosis, but its identification from clinical imaging remains challenging. X-rays and CT scans were analyzed and parameters identified that correlated to pump thrombosis. Retrospective imaging data of patients ( n = 115) with HeartmateII (HMII) or HVAD were analyzed in two groups (pump-thrombosis PT, n = 15 vs matched control group NT, n = 15) using routine X-rays and CT scans. In CT, directional deviations of the inflow cannula in three-chamber and two-chamber view (α and β angles) were identified. In HVAD PT frontal radiographs showed reduced pump body area and smaller minor axis (PT 41.3 ± 4.8 mm vs NT 34.9 ± 6.0 mm, p = 0.026), and in the lateral radiographs the visibility of the inflow cannula served as a predictive parameter for PT. In HMII patients, no parameters were associated with PT. The angle α differed significantly (NT −1.2 ± 7.5°, PT −22.0 ± 4.7°, p = 0.006) in HVAD patients. Further, correlations of x-ray parameters with CT angles α and β showed that radiographs can be used to identify malpositioned pumps. Well-aligned inflow cannula positions are essential. HVAD patients with a posterior rotation of the inflow cannula have a higher risk of pump thrombosis. This risk can reliably be identified from routine radiographs.